PENGARUH IKLIM ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN DAN DAMPAKNYA PADA KINERJA PEGAWAI DINAS KOPERASI DAN USAHA KECIL DAN MENENGAH ACEH - Fariana Fariana; Said Musnadi; M. Shabri Abdul Majid (Departemen Manajemen, Universitas Syiah Kuala, 2017)
ABSTRACT Performance is should be possessed by every employee to perform any duties and responsibilities given to the employee organization. With a good performance, any employee can resolve any burden of organizations with effective and efficient way so that the problems that occur in an organization can be overcome. To improve performance, the Office of Cooperatives and SMEs in Aceh need to pay attention to the organizational climate and employee commitment. Respondents in this study amounted to 123 persons who were employees of this organization.. The analysis method used was Path Analysis which was the development of a regression analysis which is operated by using SPSS 22. Results showed Organizational Climate, Job Satisfaction and Work Commitment affect either partially or simultaneously on Employee Performance of Department of Cooperatives and Small enterprises of Aceh. The results also show that there is a direct effect of Organizational Climate, Job Satisfaction on Employee Performance Department of Cooperatives and Small and Medium Enterprise Aceh. Keywords: Organizational Climate, Job Satisfaction, Work Commitment, Employee Performance